Best books for children, supplement to the 8th edition preschool through grade 6 - Barr, Catherine 1951-; Gillespie, John Thomas 1928-.; Barr, Catherine 1951- (Westport, Conn. Libraries Unlimited, 2007)
Offers five thousand thematically arranged reviews and recommendations for children's books up to the sixth grade, each of which includes an annotation, review citations, and bibliographic data.
Prev. edition cataloged under John T. Gillespie.
Keywords: Children's literature -- Bibliography; Children -- Books and reading -- United States; Best books -- United States